Determinan Agresivitas Pajak: Leverage, Capital Intensity, Profitabilitas - Meli Andriyani; Nera Marinda Machdar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Tax aggressiveness is a proactive action taken by many large companies to avoid tax obligations and maximize profits. Companies organize their financial activities to minimize tax costs or carry out aggressive tax planning within the limits of applicable laws to minimize tax obligations. In making scientific articles, previous research is needed. This article presents a review of what factors have an influence on Tax Aggressiveness, namely Leverage, Capital Intensity, and Profitability. This article aims to formulate a hypothesis about the relationship between variables that can be used in subsequent research. The findings from this literature review are: 1) Leverage has an impact on Tax Aggressiveness; 2) Capital Intensity has an impact on Tax Aggressiveness; and 3) Profitability has an impact on Tax Aggressiveness.